Fabrication of tough, self‐recoverable, and electrically conductive hydrogels by in situ reduction of poly(acrylic acid) grafted graphene oxide in polyacrylamide hydrogel matrix. Issue 23 (6th December 2019) - Li, Bengang; Wu, Chao; Wang, Chengyu; Luo, Zhenyang; Cao, Jianpeng
ABSTRACT: Developing electrically conductive hydrogels with good electronic properties and excellent mechanical performance is significant to their potential applications. In this article, we present a strategy to fabricate tough, self‐recoverable and electrically conductive hydrogels containing reduced graphene oxide (rGO). Poly(acrylic acid) grafted graphene oxide (GO‐g‐PAA) was synthesized and incorporated into chemically crosslinked polyacrylamide (PAM) networks to obtain GO‐g‐PAA/PAM hydrogels, which were further treated with ascorbic acid solution at ambient temperature to give rGO‐g‐PAA/PAM hydrogels. The interfacial interaction between GO/rGO and hydrogel matrix was improved by reversible hydrogen bonds between the grafted PAA chains and PAM matrix. Consequently, both GO‐g‐PAA/PAM and rGO‐g‐PAA/PAM hydrogels exhibited improved tensile properties, excellent energy dissipation, and rapid self‐recovery. The in situ chemical reduction of GO‐g‐PAA in hydrogel matrix endowed rGO‐g‐PAA/PAM hydrogels with satisfactory electrical conductivity and obvious resistance change upon stretching. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48781. Abstract : Fabrication of electrically conductive rGO‐g‐PAA/PAM hydrogels with excellent interfacial compatibility by in situ chemical reduction of GO‐g‐PAA in PAM hydrogel matrix.